Pengaruh Terpaan Iklan Media Online Produk Focallure terhadap Sikap dan Perilaku Mahasiswi Universitas Islam Makassar - Sulastri Safitri (Program of Communication Sciences, Faculty of Social and Political Sciences, UIM, 2019)
This research is a quantitative study that aims to determine the effect of online media advertising on Focallure products on the attitudes and behavior of female students at Makassar Islamic University. Respondents in this study were drawn from students from 8 faculties totaling 1,731 people. Samples selected in this study were 325 respondents with 5% precision. The research data was obtained through a survey of respondents by distributing questionnaires. Data processing and analysis is done by simple linear regression analysis using the help of the SPSS program. The results of this study indicate that there is an influence of advertising exposure on student attitudes by 44% and influence on student behavior by 26.9%